Energy-saving coating for large ethylene heating furnace and preparation method thereof
By using fake titanium ore structural ceramic materials and high-strength adhesives in heating furnace coatings, a high-strength and high-adhesion coating is formed, which solves the unstable emissivity and poor binding force of existing coatings under high temperature environments. The problem is that long life, low heat conduction and efficient heat transfer are achieved.
Patent Information
- Application Number
- CN202411595081.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The emissivity of existing heating furnace coatings is unstable under high temperature environments, and the low cohesive strength of the binder leads to poor coating bonding strength, which is prone to cracking and falling off under severe thermal stress environments, affecting service life and production efficiency.
Energy-saving coatings composed of pseudo-plate titanium ore structure thermal insulation ceramic materials, aluminum phosphate adhesives, silicon sols, etc. are used to produce fluorine topaz and needle-shaped mullite through reactions such as kaolin, aluminum hydroxide, AlF3, etc., forming high-strength glue Adhesive system, combining nano-silicon and boron carbide to improve the hardness and adhesion of the coating, and protects it from oxidation by coating silicon carbide with borosilicate.
It significantly improves the infrared emissivity and hardness of the coating, enhances the bonding force with the furnace lining, extends the service life, reduces coking phenomena and high-temperature deformation, and improves heat transfer efficiency and wear resistance.
Smart Images

Figure CN119118656B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy-saving coating preparation, and in particular to an energy-saving coating applied to a large ethylene heating furnace and a preparation method thereof. Background Art
[0002] As one of the important basic raw materials of the petrochemical industry, ethylene has many downstream derivatives, including polyethylene, ethylene glycol, ethylene oxide, styrene, polyvinyl chloride, ethylene-vinyl acetate copolymer and other chemical products. Its important role in the petrochemical industry is self-evident. In the large ethylene project, the heating furnace is the core, and its thermal efficiency directly affects the economic efficiency of the entire large ethylene project. For heating furnaces that mainly use radiation heat transfer, setting energy-saving coatings on the surface of the furnace lining can increase the surface radiation coefficient of objects involved in radiation heat transfer in the furnace, reduce the temperature of the outer wall of the furnace, and significantly improve the heat transfer process in the furnace, achieving the purpose of energy saving and efficiency improvement.
[0003] Chinese invention patent application No. 201310524263.8 discloses a heat radiation coating for a heating furnace, including a base material, an additive, an adhesive, a plasticizer and a solvent, wherein the base material and the additive are selected from five or all of zinc aluminum spinel powder, manganese aluminum spinel powder, ilmenite powder, boron carbide, iron oxide, and desiliconized zirconium powder; the adhesive is composed of liquid aluminum dihydrogen phosphate and liquid magnesium dihydrogen phosphate, the weight percentage of the base material and the additive is 6%-75%, the weight percentage of the adhesive is 5%-29%, the weight percentage of the plasticizer is 0.5%-3%, and the balance is solvent. This prior art solves the problems of weak thermal shock resistance and weak adhesion in traditional technologies, and can improve the thermal efficiency of energy utilization. However, the emissivity of the above-mentioned high-radiation coating is unstable when used, and the inability of the coating particles to be suspended in the air will result in poor penetration after spraying, which will affect its adhesion ability in a high-temperature thermal radiation environment and shorten its service life. If it will continue to be used, it will be necessary to stop the furnace for spraying again, affecting production and increasing costs. To this end, Chinese invention patent application No. 202310552843.1 discloses a high-radiation coating and spraying process for spraying the lining of a petroleum and petrochemical heating furnace, including the following raw materials: 5-6% zirconium oxide, 27-27.5% small-particle silica sol, 14-15% silicon carbide, 8.1% chromium oxide, 27-28% brown corundum, 8-8.5% potassium dihydrogen phosphate, 10-11% calcium carbonate and 1-1.5% cobalt oxide, wherein the aluminum oxide content in the brown corundum is not less than 95%; the high-radiation coating and spraying process sprayed on the lining of the petroleum and petrochemical heating furnace have high refractoriness and strong stability when used, and are not affected by acid, alkali, and salt environments. In addition, the coating can effectively penetrate, has strong adhesion, and is durable and meets the use requirements. However, silicon carbide is easily oxidized and fails at high temperatures, which is not conducive to the long-term service of infrared radiation coatings in high temperature environments. Moreover, its adhesive is silica sol, which has relatively low cohesive strength, resulting in low bonding strength and poor force between the coating and the coating base. The coating is prone to internal crack expansion under harsh thermal stress environment, which in turn causes the coating to crack or even fall off.
[0004] To this end, this application is filed. Summary of the invention
[0005] The invention aims at the problems in the prior art and discloses an energy-saving coating applied to a large ethylene heating furnace and a preparation method thereof.
[0006] On the one hand, the present invention provides an energy-saving coating for a large ethylene heating furnace, comprising the following components in percentage by mass: 20%-25% of a heat-insulating ceramic material, 22%-28% of a first filler, 20%-25% of an adhesive, 5%-10% of an additive, and the balance being deionized water;
[0007] The thermal insulation ceramic material has a pseudobrookite structure, and its general chemical formula is (Mga ,Co b ,Ni x ,Zn y )Fe z Ti2O5, wherein: a, b, x, y, z are selected from 0.18-0.20 and are the same;
[0008] The first filler contains AlF3 in an amount of not less than 25% by mass;
[0009] The adhesive is formed by mixing aluminum phosphate adhesive, silica sol and a second filler in a mass ratio of 1: (0.3-0.5): (0.5-0.7); the second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano silicon and boron carbide in a mass ratio of (1.5-2.5): (0.5-1.2): (0.5-1.0): (0.8-1.2): (0.5-1.2).
[0010] The thermal insulation ceramic material has low thermal expansion coefficient, low thermal conductivity, high thermal stability, small bandgap width and high configuration entropy, which helps electrons migrate to high energy levels after absorbing infrared radiation, thereby improving the emissivity; moreover, the introduction of trivalent iron significantly enhances the strength and hardness of the material without affecting the high emissivity. The reason may be that trivalent iron is firmly dissolved in the cation site, thus hindering the movement of dislocations in the crystal, increasing the difficulty of dislocation movement, and then improving the strength and hardness;
[0011] The adhesive contains aluminum phosphate adhesive, silica sol and a second filler. The second filler is a mixture of kaolin, aluminum hydroxide, silicon carbide, nano silicon and boron carbide. The first filler contains AlF3. Under high temperature, kaolin, aluminum hydroxide, AlF3 and SiO2 in silica sol react to generate fluorotopaz. As the reaction proceeds, the fluorotopaz is transformed into needle-shaped mullite. The fluorotopaz generated in the early stage works together with the aluminum phosphate adhesive and silica sol to play an adhesive role, promoting a firm connection between the energy-saving coating and the substrate, and then transforms into needle-shaped mullite to play the role of a rigid structural skeleton. In this process, nano Silicon and boron carbide are oxidized and expand rapidly in volume. Compounding them in the above ratio can effectively make up for the volume shrinkage problem caused by high-temperature decomposition of the adhesive. In addition, borosilicate with good fluidity and extremely high viscosity will be generated during the oxidation process. Borosilicate can wrap and protect the surface of silicon carbide to prevent it from being oxidized at high temperature. Compounding borosilicate and high-strength silicon carbide in the above ratio can fully fill the internal holes and cracks of the adhesive. Multi-point filling increases the density of the adhesive, making the overall performance of the adhesive uniform, which not only helps to improve the adhesive effect, but also significantly improves the adhesive strength.
[0012] The present invention finds that: under the synergistic effect and mutual influence of the thermal insulation ceramic material and the adhesive, the obtained energy-saving coating has high infrared emissivity and low thermal conductivity. It can not only radiate heat through high emission, but also isolate heat energy through low thermal conductivity, thereby improving the heat exchange in the furnace, increasing the intensity and uniformity of the temperature field in the furnace, and achieving energy saving and efficiency improvement. More importantly, the coating formed by the curing has high hardness and good smoothness, has a strong bonding strength with the lining of the large ethylene heating furnace, and has a long service life.
[0013] Preferably, the thermal insulation ceramic material is a pure phase high entropy ceramic material having a pseudobrookite structure, and the general chemical formula of the thermal insulation ceramic material is (Mg a ,Co b ,Ni x ,Zn y )Fe z Ti2O5, where a, b, x, y, and z are all 0.18.
[0014] Preferably, the first filler contains 30% by mass of AlF3.
[0015] Further preferably, the adhesive is formed by mixing aluminum phosphate adhesive, silica sol and a second filler in a mass ratio of 1:0.4:0.6, and the second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano-silicon and boron carbide in a mass ratio of 2:0.8:0.8:1:1.
[0016] According to the above-mentioned proportions, the generated needle-shaped mullite, fluorotopaz and borosilicate-coated silicon carbide are in appropriate proportions. The rigid structural skeleton of the needle-shaped mullite is combined with the multi-point filling of borosilicate-coated silicon carbide, which can significantly improve the adhesive strength. The in-situ synthesized adhesive fluorotopaz, aluminum phosphate adhesive and silica sol, with the assistance of silicon carbide, nano-silicon and boron carbide, together form a dense and uniform adhesive system, which ensures a stable and firm bond between the energy-saving coating and the furnace lining.
[0017] Preferably, the first filler is a mixture of one or more of zirconium oxide, dolite, mullite, and feldspar with AlF3. Zirconium oxide, dolite, mullite, and feldspar are common silicate rheological additives, which are used to improve mixing uniformity and control the viscosity of the synthesis process, and can also improve the corrosion resistance, oxidation resistance and stability of the material, and can regulate the thermal expansion of energy-saving coatings, effectively reducing the stress caused by thermal shock; the mass percentage of SiO2 in the silica sol is 10%-30%; in the second filler: the silicon carbide is a silicon carbide whisker with a diameter of 0.2-0.6µm and a whisker length of 60-100µm, the nano silicon particle size is 20-50nm, and the boron carbide is an ultrafine boron carbide with a particle size of 25-50µm; the additive is selected from one or more of a defoamer, a leveling agent, a wetting agent, a dispersant, and an anti-settling agent.
[0018] Silica sol is a dispersion of nano-scale SiO2 particles in water. When the mass percentage of SiO2 exceeds 30%, the viscosity of silica sol is high, which is not conducive to the coating of energy-saving coatings. When the mass percentage of SiO2 is less than 10%, the viscosity of silica sol is too low and the water content is too high, which will cause the adhesive to be too thin, causing the powder material to settle and stratify. The present invention finds that when the mass percentage of SiO2 in silica sol is 10%-30%, its viscosity is moderate, which not only helps various powder materials to be evenly dispersed without settling, but also does not have an adverse effect on subsequent use.
[0019] As for defoamers, leveling agents, wetting agents, dispersants, anti-settling agents, etc., they are all conventional choices in the art. For example, the defoamer can be at least one of polyether-modified polydimethylsiloxane, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether, fatty acid glyceride, and dimethyl silicone oil; the leveling agent can be a polyether-modified silicone leveling agent; the wetting agent is a mixture of polyether polyols; and the dispersant can be at least one of dispersant ox 3070, S19 dispersant, 5040 dispersant, LED-1 dispersant, S19 dispersant, and sodium lignin sulfonate.
[0020] Preferably, the working temperature of the energy-saving coating is 700-1650°C, and the thermal conductivity is 1.4-1.7 W·m -1 ·K -1 The emissivity of the obtained coating at 900°C and 3-5μm band is 0.91-0.93.
[0021] In the present invention, the thermal insulation ceramic material is the core thermal insulation material, which is solid-dissolved with the first filler at high temperature to form a solid solution with high emissivity and low thermal conductivity. Since the atomic sizes of Mg, Co, Ni, Zn, and Ti are different, the internal lattice distortion is serious. The serious lattice distortion increases the hardness of the resulting coating, and the introduction of Fe hinders the movement of dislocations in the crystal, increases the difficulty of dislocation movement, and further improves the strength and hardness. In addition, kaolin, aluminum hydroxide, silica sol and AlF3 react in situ to first generate fluorotopaz with a bonding effect. As the reaction proceeds, the fluorotopaz is converted into needle-shaped mullite that plays a rigid skeleton role. The fluorotopaz, aluminum phosphate adhesive, and silica sol obtained in the early stage work together to form a high-strength adhesive system with the assistance of silicon carbide, nano-silicon, and boron carbide. The needle-shaped mullite generated subsequently further improves the hardness and smoothness of the coating, so that the energy-saving coating and the furnace lining are stably and firmly bonded.
[0022] Compared with the existing technology, the obtained coating not only has high emissivity and low thermal conductivity, but also has high hardness, good smoothness and strong adhesion. For ethylene cracking, it can reduce coking, improve heat transfer efficiency, resist wear and high-temperature deformation, ensure coating stability and extend coating life.
[0023] On the other hand, the present invention also provides a method for preparing an energy-saving coating, comprising the following steps:
[0024] S1, mixing MgO, CoO, NiO, ZnO, Fe2O3, and TiO2 in a stoichiometric ratio as shown in the chemical formula of the thermal insulation ceramic material, then ball-milling and pressing the mixture into ceramic blocks, sintering the ceramic blocks, crushing them, and sieving them to obtain the thermal insulation ceramic material;
[0025] S2. Weigh according to the ratio, add the thermal insulation ceramic material to the adhesive, stir evenly, add a portion of deionized water, continue to stir evenly to obtain a first premix, add the first filler to the auxiliary agent, stir evenly, add the remaining portion of deionized water, continue to stir evenly to obtain a second premix, mix the first premix and the second premix and ball mill to obtain.
[0026] The preparation method of the invention is simple, easy to operate and realize, the raw material cost is low and easy to obtain, and the preparation process is environmentally friendly and pollution-free.
[0027] Preferably, in S1, MgO, CoO, NiO, ZnO, Fe2O3, and TiO2 are all of analytical grade, the ball milling medium is zirconia balls, the ball-to-material ratio is (3-5):1, the ball milling speed is 300-500r / min, the ball milling time is 3-5h, the sintering temperature is 1250-1350°C, the time is 30-90min, and the aperture of the sieve used for screening is 100-300 mesh.
[0028] Preferably, in S2, the ball milling medium is zirconia balls, the ball-to-material ratio is (3-5):1, the ball milling speed is 500-800 r / min, and the ball milling time is 5-8 h.
[0029] Preferably, in S2, 1 / 2 of deionized water is added when preparing the first premix, and the remaining 1 / 2 of deionized water is added when preparing the second premix. The stirring operations involved in preparing the first premix and the second premix are all mechanically stirred, the stirring speed is 5000-8000 rpm, and the stirring time is not less than 30 minutes.
[0030] It should be noted that:
[0031] (1) Before using the energy-saving coating, the relevant parts of the heating furnace need to be pretreated, and the pretreatment at least includes removing impurities on the surface of the furnace lining and leveling the surface of the furnace lining;
[0032] (2) When the energy-saving coating is used, it can be applied to the heating furnace lining by any existing coating method such as dipping, spraying, roller coating, brushing, etc., and the thickness is preferably not more than 2 mm. The heating furnace lining materials include but are not limited to refractory bricks, refractory fibers, ceramic fiber modules, ceramic fiber felts, ceramic fiber blankets, ceramic fiber boards, and any other existing heating furnace lining materials developed around the core component of alumina;
[0033] (3) After the energy-saving coating is set on the lining of the heating furnace, it is dried at room temperature and the energy-saving coating is formed as the furnace is heated; preferably, sintering is carried out on the basis of drying at room temperature, and a programmed heating method is adopted during sintering, and the heating rate does not exceed 10°C / min. After heating to 780-850°C, it is kept warm for 2.5-4h, and then the temperature is further increased to 1000-1200°C and kept warm for 1-2h, and then naturally cooled. According to this sintering method, a continuous, complete, smooth, dense, non-blistering, non-cracking, and non-edge warping coating can be obtained. Of course, sintering is not a necessary step. Even if sintering is not performed, in the subsequent use of the heating furnace, the energy-saving coating set will also heat up with the furnace and form a coating under heat. However, due to the different temperatures at different positions of the heating furnace lining, the composition of the formed coating may be different and unevenly distributed on the surface of the lining, and the optimal performance cannot be achieved. This may affect the physical properties of the coating, making it unsuitable for use in harsh thermal stress environments, and lead to poor energy-saving and efficiency-enhancing effects.
[0034] Compared with the prior art, the coating formed after the energy-saving coating proposed by the present invention is set on the surface of the heating furnace lining can not only improve the surface radiation coefficient of the objects participating in radiation heat transfer in the furnace, reduce the temperature of the outer wall of the furnace, and significantly improve the heat transfer process in the furnace, thereby achieving the purpose of energy saving and efficiency improvement, but also has high hardness, good smoothness and strong adhesion. For ethylene cracking, it can reduce coking, improve heat transfer efficiency, resist wear and high-temperature deformation, ensure the stability of the coating and extend the life of the coating, thereby improving the production efficiency and product quality of ethylene cracking. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is the XRD diagram of the thermal insulation ceramic material in Example 1.
[0037] Figure 2 This is a test chart of the emissivity of the product of Example 1 in the 2.5-5μm band at 900°C.
[0038] Figure 3 This is a photo of the radiation chamber furnace without energy-saving paint.
[0039] Figure 4 This is a photo of the radiation chamber furnace sprayed with energy-saving paint. DETAILED DESCRIPTION
[0040] In order to facilitate understanding of the technical solution of the present invention, a high-temperature sealing adhesive of the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0041] The aluminum phosphate adhesive used in the following examples and comparative examples is prior art, specifically obtained by self-production, and the preparation method is: 85wt% concentrated phosphoric acid is diluted with water to a concentration of 55wt% dilute phosphoric acid, then heated to 90°C and kept warm, and aluminum hydroxide is slowly added while maintaining mechanical stirring and fully stirred for 1h, wherein the molar ratio of Al(OH)3 to H3PO4 is 1:0.5.
[0042] The auxiliary agents used in the following examples and comparative example 1 specifically include dispersants, defoamers and wetting agents. The dispersant specifically uses dispersant ox 3070, the defoamer specifically uses polyoxyethylene polyoxypropanolamine ether, and the wetting agent specifically uses METOLAT 388 water-based coating wetting dispersant provided by Beijing Dongfang Aohan Company. In the following examples and comparative examples: MgO, CoO, NiO, ZnO, Fe2O3, and TiO2 are all analytical grade, with a pore size of 100-300 mesh; silicon carbide is a silicon carbide whisker with a diameter of 0.2-0.6µm and a whisker length of 60-100µm, the nano silicon particle size is 20-50nm, and the boron carbide particle size is 25-50µm.
[0043] Other various chemical raw materials involved in the following examples and comparative examples are all commercially available and the manufacturers have no special requirements.
[0044] Unless otherwise specified, the characterization methods and characterization conditions involved in the following examples and comparative examples are conventional characterization methods and conventional characterization conditions.
[0045] The "sintering" in the performance tests involved in the following examples and comparative examples is specifically: using a programmed heating method, the heating rate is 4°C / min, the temperature is raised to 820°C and then kept at this temperature for 3 hours, then the temperature is further raised to 1100°C and then kept at this temperature for 1.5 hours, and then the temperature is naturally lowered. The "spraying" process involved in the following performance tests is powered by compressed air, and the spraying pressure is 1.2kg.f / cm 2 , spraying thickness 1mm.
[0046] Example 1
[0047] An energy-saving coating for a large ethylene heating furnace comprises the following components in percentage by mass: 23% of a heat-insulating ceramic material, 25% of a first filler, 22% of an adhesive, 8% of an additive (2% of a dispersant, 3% of a defoamer, and 3% of a wetting agent), and the balance is deionized water;
[0048] The thermal insulation ceramic material is a pseudobrookite structure, with a general chemical formula (Mg 0.18 ,Co 0.18 ,Ni 0.18 ,Zn 0.18 )Fe 0.18 Ti2O5;
[0049] The first filler is a mixture of zirconium oxide, daphne and AlF3, the mass ratio of zirconium oxide to daphne is 1:2, and the mass percentage of AlF3 in the first filler is 30%;
[0050] The adhesive is formed by mixing aluminum phosphate adhesive, silica sol and a second filler in a mass ratio of 1: 0.4:0.6, the mass percentage of SiO2 in the silica sol is 20%, and the second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano silicon and boron carbide in a mass ratio of 2: 0.8: 0.8: 1:1.
[0051] The preparation method of the energy-saving coating comprises the following steps:
[0052] S1, MgO, CoO, NiO, ZnO, Fe2O3, TiO2 according to (Mg 0.18 ,Co 0.18 ,Ni 0.18 ,Zn 0.18 )Fe 0.18 Ti2O5 is mixed in the stoichiometric ratio shown in FIG. 1 , and then ball-milled with zirconium oxide balls as ball-milling media and pressed into ceramic blocks. During ball-milling, the ball-to-material ratio is 4:1, the ball-milling speed is 400 r / min, and the ball-milling time is 4 h. The ceramic blocks are sintered, crushed, and sieved in sequence. The sintering temperature is 1300° C., the sintering time is 1 h, and the aperture of the sieve used for sieving is 100-300 meshes, thereby obtaining the thermal insulation ceramic material.
[0053] S2. Weigh according to the ratio, add the thermal insulation ceramic material to the adhesive consisting of aluminum phosphate adhesive, silica sol and the second filler, stir at 6000 r / min for 30 min, add 1 / 2 deionized water, continue to stir at 6000 r / min for 40 min to obtain a first premix, add the first filler to the auxiliary agent, stir at 6000 r / min for 30 min, add the remaining deionized water, continue to stir at 6000 r / min for 40 min to obtain a second premix, mix the first premix and the second premix and ball mill, the ball milling medium is zirconia balls, the ball-to-material ratio is 5:1, the ball milling speed is 800 r / min, and the ball milling time is 8 hours.
[0054] The thermal insulation ceramic material obtained by S1 was subjected to XRD detection, such as Figure 1 As shown: Example 1 shows that a new high entropy ceramic material is obtained, and its crystal structure is consistent with CoTi2O5 shown in PDF#76-1600. Figure 2 As shown: The emissivity test of the energy-saving coating obtained in Example 1 shows that the emissivity is 0.89-0.93 at 900°C in the 2.5-5μm band, and is relatively stable in the 3-5μm band; in addition, it has been verified that the infrared attenuation rate of the high-entropy ceramic material is less than 1%, which helps to maintain good infrared radiation performance for a long time. Furthermore, according to the requirements of the ASTME1461-13 (2022) test standard, the energy-saving coating obtained in Example 1 is sprayed on the surface of the refractory brick, and the thermal conductivity of the coating at 900°C is only 0.77W / mK.
[0055] In order to further verify the energy-saving effect of the energy-saving coating proposed in the present invention, the energy-saving coating obtained in Example 1 was sprayed on the surface of the radiation chamber of two ethylene cracking furnaces of the same manufacturer and the same specifications. The photos before and after spraying are as follows: Figure 3 and Figure 4 The coating is gray-green, and the treatment volume, exhaust gas temperature, and furnace temperature before and after use are counted. The specific results are shown in Table 1.
[0056] Table 1
[0057]
[0058] It can be seen from Table 2 that after the energy-saving coating proposed in Example 1 was used in the radiation chamber furnace of the ethylene cracking furnace, both the exhaust gas temperature and the furnace temperature were significantly reduced, and the energy-saving and emission reduction effects were excellent. Moreover, after continuous use for 14 months, the energy-saving and emission reduction effects remained basically the same. Observation of the coating found that it was still intact after 14 months of use, without cracks, bubbles, or warping, and was well bonded to the furnace lining.
[0059] Example 2
[0060] Compared with Example 1, the component contents of the energy-saving coating are adjusted, specifically including the following components in mass percentage: 20% thermal insulation ceramic material, 28% first filler, 20% adhesive, 10% additive (2% dispersant, 4% defoamer, 4% wetting agent), and the balance is deionized water. The rest are the same as in Example 1.
[0061] Example 3
[0062] Compared with Example 1, the component contents of the energy-saving coating are adjusted, specifically including the following components in mass percentage: 25% thermal insulation ceramic material, 22% first filler, 25% adhesive, 5% additive (1% dispersant, 2% defoamer, 2% wetting agent), and the balance is deionized water. The rest are the same as in Example 1.
[0063] Example 4
[0064] Compared with Example 1, the thermal insulation ceramic material is different, and its chemical formula is specifically (Mg 0.19 ,Co 0.19 ,Ni 0.19 ,Zn 0.19 )Fe 0.19 Ti2O5, and the rest are consistent with Example 1.
[0065] Example 5
[0066] Compared with Example 1, the thermal insulation ceramic material is different, and its chemical formula is specifically (Mg 0.2 ,Co 0.2 ,Ni 0.2 ,Zn 0.2 )Fe 0.2 Ti2O5, and the rest are consistent with Example 1.
[0067] Example 6
[0068] Compared with Example 1, the component content of the adhesive is adjusted. The adhesive is prepared by mixing aluminum phosphate adhesive, silica sol and the second filler in a mass ratio of 1:0.5:0.5. The rest is consistent with Example 1.
[0069] Example 7
[0070] Compared with Example 1, the component content of the adhesive is adjusted. The adhesive is prepared by mixing aluminum phosphate adhesive, silica sol and the second filler in a mass ratio of 1:0.3:0.7. The rest is consistent with Example 1.
[0071] Example 8
[0072] Compared with Example 1, the component content of the second filler is adjusted. The second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano silicon and boron carbide in a mass ratio of 2.5:1:0.5:1.2:1.
[0073] Example 9
[0074] Compared with Example 1, the component content of the second filler is adjusted. The second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano-silicon and boron carbide in a mass ratio of 2:0.5:1:1:0.5.
[0075] Example 10
[0076] Compared with Example 1, the component content of the second filler is adjusted. The second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano silicon and boron carbide in a mass ratio of 1.5:1.2:0.8:0.8:1.2.
[0077] Embodiment 11
[0078] Compared with Example 1, the mass percentage of SiO2 in the silica sol is adjusted from 20% to 10%, and the rest is consistent with Example 1.
[0079] Example 12
[0080] Compared with Example 1, the mass percentage of SiO2 in the silica sol is adjusted from 20% to 30%, and the rest is consistent with Example 1.
[0081] Comparative Example 1
[0082] Compared with Example 1, the thermal insulation ceramic material is replaced with an equal amount of silicon carbide.
[0083] Comparative Example 2
[0084] Compared with Example 1, the mass percentage of the thermal insulation ceramic material is adjusted from 23% to 15%, and the rest is consistent with Example 1.
[0085] Comparative Example 3
[0086] Compared with Example 1, the mass percentage of the thermal insulation ceramic material is adjusted from 23% to 30%, and the rest is consistent with Example 1.
[0087] Comparative Example 4
[0088] Compared with Example 1, the mass percentage of AlF3 in the first filler is 20%, and the rest is consistent with Example 1.
[0089] Comparative Example 5
[0090] Compared with Example 1, the mass percentage of SiO2 in the silica sol is adjusted from 20% to 5%, and the rest is consistent with Example 1.
[0091] Comparative Example 6
[0092] Compared with Example 1, the mass percentage of SiO2 in the silica sol is adjusted from 20% to 40%, and the rest is consistent with Example 1.
[0093] Comparative Example 7
[0094] Compared with Example 1, the second filler does not contain silicon carbide, nano-silicon, and boron carbide, and the contents of other components are consistent with those in Example 1.
[0095] Comparative Example 8
[0096] Compared with Example 1, the first filler does not contain AlF3, and the rest is consistent with Example 1.
[0097] According to the following operation, various performance tests were performed on the products obtained in various embodiments and comparative examples, and the specific performances are as follows:
[0098] (1) Thermal stability test
[0099] According to the test standard GB / T 1735-2009 "Determination of Heat Resistance of Paints and Varnishes", the energy-saving coatings obtained in each embodiment and comparative example were sprayed on refractory bricks, then sintered, and finally placed in an air atmosphere of a box furnace. After a 1000-hour thermal stability test at 1500°C, the surface of the coating was observed.
[0100] (2) Corrosion resistance test
[0101] First, the products of each embodiment and comparative example were brushed on the surface of the alumina crucible sheet for at least 3 times, with a coating thickness of 2 mm, and then sintered; a saturated salt solution of Na2SO4 and K2SO4 with a mass ratio of 19:1 was prepared and brushed on the coating surface to make the salt film mass 10 mg / cm 2 , and then put the sample into a resistance furnace, heated to 700℃ for 240 hours of corrosion test, and observe the surface of the obtained coating.
[0102] (3) Thermal shock resistance test
[0103] According to the test standard GB / T 30873-2014 "Test method for thermal shock resistance of refractory materials", the obtained energy-saving coating was sprayed on the refractory bricks and then sintered. The coating was heated to 1300℃ and then water quenched. This process was repeated until the coating was damaged, and the number of repetitions was recorded.
[0104] (4) Emissivity test
[0105] According to GB / T 4653-1984 "Infrared emissivity of coatings" standard, the obtained energy-saving coatings were tested and their normal emissivity at 900°C and 3-5μm band was counted.
[0106] (5) Hardness
[0107] The pencil hardness is tested in accordance with the provisions of GB / T6739-2006 Paints and varnishes: Determination of paint film hardness by pencil method.
[0108] (6) Thermal expansion coefficient test
[0109] According to the test standard GB / T 7320-2018 "Coefficient of Thermal Expansion of Coatings", the obtained energy-saving coating was sprayed on the refractory bricks, and its linear thermal expansion coefficient was tested within 25-800°C after sintering.
[0110] (7) Adhesion test
[0111] Adhesion was measured in accordance with the provisions of GB / T1720-1988 Determination of paint film adhesion, using the cross-cut method for testing.
[0112] Among them, after the thermal stability test and the corrosion resistance test, the coatings of each embodiment were processed, and the coating surface and coating cross section were observed under a microscope. The observation results showed that the coating surface of each embodiment was smooth, dense, without blistering, cracking, and warping, and was well combined with the substrate. It can be seen that the energy-saving coating proposed by the present invention has good thermal stability and corrosion resistance. The coatings of each comparative example have more or less blistering, cracking, and warping.
[0113] The test results of emissivity, hardness, thermal expansion coefficient and adhesion of each embodiment and comparative example are shown in Table 2 below.
[0114] Table 2
[0115]
[0116] As shown in Table 2:
[0117] It can be seen from the test results of Examples 1 to 12 that the energy-saving coatings prepared according to the preparation method defined in the present invention have good thermal shock resistance, high emissivity, high hardness, low expansion coefficient and strong adhesion, and can meet the requirements for use in large ethylene heating furnaces.
[0118] It can be seen from the test results of Comparative Example 1 and Example 1 that when the insulating ceramic material proposed by the present invention is used to replace the traditional high-radiation material silicon carbide, the emissivity can be maintained basically close to that of the conventional high-radiation material silicon carbide, and the thermal shock resistance and hardness are significantly improved. Since the insulating ceramic material is stable at high temperatures and will not be oxidized, it can be predicted that Example 1 has a longer service life. Moreover, the content of the insulating ceramic material needs to be controlled within an appropriate range. If it is too little (Comparative Example 2), the emissivity of the coating will be adversely affected due to the low content. If it is too much (Comparative Example 3), the viscosity of the energy-saving coating will be reduced and the uniformity will be poor due to the reduction in the relative content of the adhesive. Although the fluidity is good, it is not conducive to the improvement of the emissivity. In addition, the excessively high content will lead to poor bonding with the coating, resulting in poor adhesion and thermal shock resistance.
[0119] In addition, the mass percentage of AlF3 in the first filler, the mass percentage of SiO2 in the silica sol, and the silicon carbide, nano silicon, and boron carbide in the second filler all have a significant effect on the physical properties of the coating. As shown in Comparative Examples 4, 5, and 7: When the mass percentage of AlF3 in the first filler is too low or the mass percentage of SiO2 in the silica sol is too low or silicon carbide, nano silicon, and boron carbide are not added, it is not conducive to the formation of fluorotopaz and needle-shaped mullite, and thus leads to the degradation of the thermal shock resistance, hardness, and adhesion of the coating. Obviously, the reason why the coating has good thermal shock resistance, high hardness, and strong adhesion is the result of the synergistic effect of the above three technical parameters, and any one or two technical means will not bring about significant improvement in the above performance. Moreover, if the mass percentage of SiO2 in the silica sol is too high, the overall viscosity of the energy-saving coating will be too large and the fluidity will be poor. The thickness should not be controlled during coating, and the risk of cracking of the coating in a harsh thermal stress environment is high.
[0120] In summary, the energy-saving coating proposed in the present invention has an emissivity of 0.91-0.93 in the 3-5μm band and at 900°C, and has good high temperature resistance, corrosion resistance, and thermal shock resistance. The formed coating has high hardness, strong adhesion, good smoothness, and a long service life. It has good thermal expansion matching with the substrate and can better adapt to harsh thermal stress environments. When it is used for the lining of a heating furnace, it can increase the surface radiation coefficient of objects participating in radiation heat transfer in the furnace, reduce the temperature of the outer wall of the furnace, and significantly improve the heat transfer process in the furnace, thereby significantly saving energy and increasing efficiency.
[0121] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An energy-saving coating for a large ethylene heating furnace, characterized in that: The invention comprises the following components in percentage by mass: 20%-25% of thermal insulation ceramic material, 22%-28% of first filler, 20%-25% of adhesive, 5%-10% of auxiliary agent, and the balance is deionized water; the first filler is a mixture of one or more of zirconium oxide, mullite, and feldspar and AlF3; the auxiliary agent is selected from one or more of defoaming agent, leveling agent, wetting agent, dispersant, and anti-settling agent; the thermal insulation ceramic material has a pseudobrookite structure, and its general chemical formula is (Mg a ,Co b ,Ni x ,Zn y )Fe z Ti2O5, wherein: a, b, x, y, z are selected from 0.18-0.20 and are the same; The first filler contains AlF3 in an amount of not less than 25% by mass; The adhesive is formed by mixing aluminum phosphate adhesive, silica sol and a second filler in a mass ratio of 1: (0.3-0.5): (0.5-0.7), and the second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano silicon and boron carbide in a mass ratio of (1.5-2.5): (0.5-1.2): (0.5-1.0): (0.8-1.2): (0.5-1.2); The preparation method comprises the following steps: S1, mixing MgO, CoO, NiO, ZnO, Fe2O3, and TiO2 in a stoichiometric ratio as shown in the chemical formula of the thermal insulation ceramic material, then ball-milling and pressing the mixture into ceramic blocks, sintering the ceramic blocks, crushing them, and sieving them to obtain the thermal insulation ceramic material; S2. Weigh according to the ratio, add the thermal insulation ceramic material to the adhesive, stir evenly, add a portion of deionized water, continue to stir evenly to obtain a first premix, add the first filler to the auxiliary agent, stir evenly, add the remaining portion of deionized water, continue to stir evenly to obtain a second premix, mix the first premix and the second premix and ball mill to obtain.
2. The energy-saving coating according to claim 1, characterized in that: The thermal insulation ceramic material is a pure phase high entropy ceramic material with a pseudobrookite structure, and the general chemical formula of the thermal insulation ceramic material is (Mg a ,Co b ,Ni x ,Zn y )Fe z Ti2O5, where a, b, x, y, and z are all 0.
18.
3. The energy-saving coating according to claim 2, characterized in that: The first filler contains 30% by mass of AlF3.
4. The energy-saving coating according to claim 3, characterized in that: The adhesive is formed by mixing aluminum phosphate adhesive, silica sol and a second filler in a mass ratio of 1: 0.4:0.6, and the second filler is formed by mixing kaolin, aluminum hydroxide, silicon carbide, nano silicon and boron carbide in a mass ratio of 2: 0.8: 0.8: 1:
1.
5. The energy-saving coating according to any one of claims 1 to 4, characterized in that: The mass percentage of SiO2 in the silica sol is 10%-30%; In the second filler: the silicon carbide is a silicon carbide whisker with a diameter of 0.2-0.6µm and a whisker length of 60-100µm, the nano-silicon particle size is 20-50nm, and the boron carbide particle size is 25-50µm.
6. The energy-saving coating according to claim 5, characterized in that: The working temperature of the energy-saving coating is 700-1650°C, and the thermal conductivity is 1.4-1.7 W·m -1 ·K -1 The emissivity of the obtained coating at 900°C and 3-5μm band is 0.91-0.
93.
7. A method for preparing the energy-saving coating according to claim 1, characterized in that: The steps are as follows: S1, mixing MgO, CoO, NiO, ZnO, Fe2O3, and TiO2 in a stoichiometric ratio as shown in the chemical formula of the thermal insulation ceramic material, then ball-milling and pressing the mixture into ceramic blocks, sintering the ceramic blocks, crushing them, and sieving them to obtain the thermal insulation ceramic material; S2. Weigh according to the ratio, add the thermal insulation ceramic material to the adhesive, stir evenly, add a portion of deionized water, continue to stir evenly to obtain a first premix, add the first filler to the auxiliary agent, stir evenly, add the remaining portion of deionized water, continue to stir evenly to obtain a second premix, mix the first premix and the second premix and ball mill to obtain.
8. The method for preparing the energy-saving coating according to claim 7, characterized in that: In S1, MgO, CoO, NiO, ZnO, Fe2O3 and TiO2 are all of analytical grade, the ball milling medium is zirconia ball, the ball-to-material ratio is (3-5):1, the ball milling speed is 300-500r / min, the ball milling time is 3-5h, the sintering temperature is 1250-1350℃, the time is 30-90min, and the aperture of the sieve used for screening is 100-300 mesh.
9. The method for preparing the energy-saving coating according to claim 7, characterized in that: In S2, the ball milling medium is zirconia ball, the ball-to-material ratio is (3-5):1, the ball milling speed is 500-800 r / min, and the ball milling time is 5-8 h.
10. The method for preparing the energy-saving coating according to claim 7, characterized in that: In S2, 1 / 2 of deionized water is added when preparing the first premix, and the remaining 1 / 2 of deionized water is added when preparing the second premix. The stirring operations involved in preparing the first premix and the second premix are all mechanically stirred, with a stirring speed of 5000-8000 rpm and a stirring time of not less than 30 min.
Citation Information
Patent Citations
A heat radiation coating for heating furnaces
CN103525142B
High-radiation coating sprayed on furnace lining of petroleum and petrochemical heating furnace and spraying process
CN116589290A
Preparation method of aluminum titanate sintering body
CN102936135A
High temperature, contamination and slagging resistant ceramic paint as well as preparation method and application of high temperature, contamination and slagging resistant ceramic paint
CN104446325A